Effect of bibliotherapy on the cognitive reasoning of children with mild intellectual disorder in public special-need schools in Ogun State - Osoba, Monisola. A.; Aramide, K. A.; Komolafe, S. F. (Communicate: Journal of Library and Information Science, 2025)
Cognitive reasoning (CR) is a critical aspect of human intelligence, encompassing the mental processes utilised for thinking, learning, and comprehending, which are essential for academic achievement. This article explores the effects of bibliotherapy on cognitive reasoning among CWMID in public special-need schools in Ogun State, Nigeria. The study adopts a pretest, posttest quasi-experimental design Purposive sampling technique was adopted, and all 22 educable children with mild intellectual disorder, aged 6-16 years, from two special-need schools in Ogun State participated in the study. Analysis of covariance was used to analyse the data collected. The study was able to establish that bibliotherapy improved cognitive reasoning among children with mild intellectual disorder in the schools for children with special needs, Ogun State, Nigeria. The treatment strategy is therefore recommended to be adopted for improving cognitive reasoning among children with mild intellectual disorder